THE INFLUENCE OF ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT AND PROACTIVE WORK BEHAVIOR AMONG EMPLOYEES OF THE NGAWI REGENCY INSPECTORATE - Rizki Timur Rahmawati; Dhani Ichsanuddin Nur; Tri Kartika Pertiwi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The objective of this research is to explore how organizational support influences the performance of employees at the Inspectorate of Ngawi Regency, either directly or through the involvement of Employee engagement and proactive work behavior. The research population consists of all 59 civil servants at the Inspectorate of Ngawi Regency, including 53 permanent civil servants (PNS) and 6 candidates (CPNS), all of whom were sampled using a census method. Data were analyzed utilizing the Partial Least Squares (PLS) statistical framework. Results revealed a significant positive relationship between organizational support and employee performance (p < 0.05). The mediation analysis confirmed that employee engagement serves as a significant mediator in this relationship, whereby organizational support influences performance through its effect on work engagement levels. Proactive work behavior is also proven to mediate this relationship, with organizational support encouraging employees to take initiative and act proactively, thereby enhancing overall performance.